Analysis and Monitoring Results of a Building Integrated Photovoltaic Façade Using PV Ceramic Tiles in Taiwan - Yen-Chieh Huang; Chi-Chang Chan; Szu-Chi Kuan; Shui-Jinn Wang; Shin-Ku Lee (International Journal of Photoenergy)
Single-crystal silicon-based solar cells laminated with tempered-glass and ceramic tiles for use in a building’s façade have been developed. The optical, thermal, and electrical properties of the proposed PV module are first evaluated, and then a wind-resistance test is carried out to evaluate the feasibility of installing it in Taiwan. The electrical and deflection characteristics of the proposed PV module did not change significantly after a 50 thermal cycling test and a 200-hour humidity-freeze test, based on IEC 61215 and a wind-resistance test. Finally, the electrical power generation ability of the proposed BIPV system with 1 kWp electrical power capacity was examined. Building information modeling software tools were used to simulate the BIPV system and carry out the energy analysis. The simulation results show a very consistent trend with regard to the actual monthly electricity production of the BIPV system designed in this work. The BIPV system was able to produce an accumulative electrical power of 185 kWh during the 6-month experimental period. In addition, the exterior temperature of the demonstration house was about 10°C lower than the surface of the BIPV system, which could reduce indoor temperature.